Análise de estabilidade de talude utilizando o método de Scanline em uma pedreira de diabásio - (:unkn) unknown (Universidade Federal do Pampa, 2021)
Geotechnics understand the dynamics of rocks, soils and buildings through the analysis of their physical and mechanical characteristics. The present work consists of the study of slope stability in a diabase mining project. In carrying out the work, the Scanline methodology was applied, for data collection, in order to obtain the classification of the rock mass through RQD (Rock Quality Designation) and RMR (Rock Mass Rating). Later, through kinematic analysis with stereographic projection, using the Dips Rocscience software, the possibilities of planar failure, wedge and toppling were defined. Subsequently, a safety factor was generated through the Slide Rocscience software, applying the Generalized Hoek-Brown criterion. As a result of the methodologies employed, it was noted that the rockmass is classified as of good quality, presenting a low risk of failure and a satisfactory safety factor according to the Brazilian standards for slope stability.
Keywords: Geotecnia; Scanline; Estabilidade de taludes; Fator de segurança; Análise cinemática; Geotechnics; Slope stability; Kinematic analysis; Safety factor; CNPQ::CIENCIAS EXATAS E DA TERRA